PERANCANGAN APLIKASI PENYISIPAN CITRA BERWARNA PADA QR CODE DENGAN METODE HALFTONE - indrafani J. Panjaitan; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The project is made in the form of a software application that accepts input color image to be processed into Halftone QR-Code. Halftone QR-Code is a composite image of the QR-Code and halftone image that can be recognized by QR-Code Scanner. QR-Code image generated using the Library Massagingtoolkit-QRCode with alphanumeric text input degan various versions QR-Code in accordance with a lot of character input. The input image is processed into a halftone image with methods Ordered Dithering variation dither matrix 4 x 4 and 8 x 8. The image of the QR-Code and halftone images will be processed into QR-Code Halftone Pattern Assignment method. Output generated by the application Halftone QR-Code tested with QR-Code ZXing Library and QRAFTER application on Iphone 6s Plus and QR. The average rate of overall success with the test scenario ZXing QR-Code Library by 94%. The average rate of overall success with the test scenario QRAFTER application on Iphone 6s Plus from the laptop screen and hardcopy respectively by 100%.